MANAJEMEN KOMUNIKASI DALAM PENINGKATAN PELAYANAN PERIZI0NAN BERBASIS DARING PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN PELALAWAN - Silfa, Syarifah Alfina; Yozani, Ringgo Eldapi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The development of digital technology has encouraged government agencies, including the Office of Investment and One-Stop Integrated Services (DPMPTSP) of Pelalawan Regency, to adopt online licensing service systems through the Online Single Submission Risk-Based Approach (OSS RBA). However, the implementation of this service still faces challenges, such as limited internal coordination, lack of effective communication media, and limited human resources. This study aims to analyze communication management in improving online licensing services at DPMPTSP Pelalawan Regency, focusing on communication planning, message management, media selection, and communication evaluation. This research employs a descriptive qualitative method with a constructivist paradigm. Data were obtained through in-depth interviews with key informants, direct observation, and the review of official documents related to the implementation of the OSS RBA system. The data analysis process was carried out through stages of data reduction, data presentation, and inductive conclusion drawing. The main focus of this research is directed at four aspects of communication management, namely communication planning, message management, media selection, and communication evaluation. The results of the study show that the implementation of communication management at DPMPTSP Pelalawan Regency is still not optimal. Communication planning has not been systematically arranged, message management is still one-way, online communication media have not been maximally utilized, and communication evaluation has not become part of the organizational routine. The main inhibiting factors include the lack of HR training, uneven workload distribution, and limitations in technological infrastructure and interdepartmental coordination. Therefore, more structured and collaborative communication strategies are needed to support the successful transformation of digital-based public services. Key Word : Communication Management, Online Licensing Services, DPMPTSP Pelalawan Regency